2021
DOI: 10.2106/jbjs.20.01805
|View full text |Cite
|
Sign up to set email alerts
|

Lower 1-Year Postoperative Mortality After Acetabular Versus Proximal Femoral Fractures in Elderly Patients

Abstract: Background:Geriatric acetabular fractures are becoming more common due to demographic changes. Compared with proximal femoral fractures, surgical treatment is more complex and often does not allow full-weight-bearing. The aims of this study were to compare operatively treated acetabular and proximal femoral fractures with regard to (1) cumulative 1-year mortality, (2) perioperative complications, and (3) predictive factors associated with a higher 1-year mortality.Methods:This institutional review board-approv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 69 publications
(169 reference statements)
0
3
0
Order By: Relevance
“…Khoshbin et al [ 3 ] from the University of Toronto in a matched cohort study that included patients older than 60 years, concluded that acetabular fractures had a much higher risk of early mortality compared to hip fractures. On the other hand, Stetzelberger et al [ 4 ] from Switzerland documented that whilst there was no difference in mortality between the acetabular and hip fracture patients at the first 30 postinjury days, the 1-year mortality was double for hip fracture patients (18% acetabular vs 36% hip fractures). Mortality has also been studied by comparing operative vs no-operative management.…”
Section: Introductionmentioning
confidence: 99%
“…Khoshbin et al [ 3 ] from the University of Toronto in a matched cohort study that included patients older than 60 years, concluded that acetabular fractures had a much higher risk of early mortality compared to hip fractures. On the other hand, Stetzelberger et al [ 4 ] from Switzerland documented that whilst there was no difference in mortality between the acetabular and hip fracture patients at the first 30 postinjury days, the 1-year mortality was double for hip fracture patients (18% acetabular vs 36% hip fractures). Mortality has also been studied by comparing operative vs no-operative management.…”
Section: Introductionmentioning
confidence: 99%
“…Failed fixations of proximal femoral fractures (PFFs) are infrequent but distressing and incapacitating complications and may be frequently accompanied by persistent pain, dysfunction, poor quality of life, and even life threatening [1][2][3]. With the expansion of surgical indications for total hip replacements (THRs) [4], it is expected to increase the demand for THRs, which are a universal and reliable procedure characteristically executed for the reduction of hip symptoms and have been approved as a surgical protocol for converting a failed fixation of PFFs with the aim of relieving pain, strengthening stability, and restoring function [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Level of evidence: Prognostic Level III F ractures of the acetabulum (AO/OTA 62A-C) in the elderly are associated with prolonged hospital stays, perioperative complications, 30-day mortality of between two and seven percent, and 1-year mortality rates of between and eight and 20%. [1][2][3][4][5] Treatment can be nonsurgical or surgical. Surgical treatment options include open reduction and internal fixation (ORIF), closed reduction and percutaneous fixation, total hip arthroplasty (THA), and combined ORIF-THA.…”
mentioning
confidence: 99%